Cost Allocation in PPP Projects: An Analysis Based on the Theory of “Contracts as Reference Points” - Yichen Peng; Jing Zhou; Qiang Xu; Xiaoling Wu (Discrete Dynamics in Nature and Society)
In recent years, the demand for infrastructure has been largely driven by the economic development of many countries. PPP has proved to be an efficient way to draw private capital into public utility construction, where ownership allocation becomes one of the most important clauses to both the government and the private investor. In this paper, we establish mathematical models to analyze the equity allocation problem of PPP projects through a comparison of the models with and without the effects of the theory of “contracts as reference points.” We then derive some important conclusions from the optimal solution of the investment ratio.